Deformation behaviors of Cu bicrystals with an inclined twin boundary at multiple scales. Issue 7 (July 2017) - Li, L.L.; Zhang, Z.J.; Zhang, P.; Tan, J.; Yang, J.B.; Zhang, Z.F.
Abstract: Cu bicrystals of different sizes with a sole twin boundary (TB) inclined at 45° with respect to the loading direction were deformed under unidirectional and cyclic loading, respectively. It is found that the slip bands (SBs) parallel to the TB can be activated near the TB at all scales without obeying the Schmid's law. It is concerned with the local stress enhancement in the macroscale while it is more closely related to the scarce dislocation sources in the microscale. Moreover, a wedge-shaped zone formed near the TB in the microscale ascribed to the limited specimen size.